Flavans and other chemical constituents of Crinum biflorum (Amaryllidaceae). (December 2019) - Kianfé, Boris Y.; Teponno, Rémy B.; Kühlborn, Jonas; Tchuenguem, Roland T.; Ponou, Beaudelaire K.; Helaly, Soleiman E.; Dzoyem, Jean P.; Opatz, Till; Tapondjou, Léon A.
Abstract: The ethyl acetate extract from the whole plant of Crinum biflorum Rottb. Showed a moderate activity against Enterococcus faecalis . Its phytochemical investigation led to the isolation of a new flavan-3-ol derivative namely (2 R, 3 R )-3-hydroxy-7-methoxy-3′, 4′-methylenedioxyflavan, together with (2 S )-7-hydroxy-3′, 4′-methylenedioxyflavan, (2 R, 3 R )-7-methoxy-flavan-3-ol, (2 S )-7-hydroxy-3′, 4′-dimethoxyflavan, 3′, 7-dihydroxy-4′-methoxyflavan, 4′, 7-dimethoxy-3′-hydroxyflavan, farrerol, β -sitosterol, β -sitosterol-3- O - β -D-glucopyranoside, oleanolic acid, kaempferol, pancratistatin, lupeol, aurantiamide acetate, Narciprimine and 2, 3-dihydroxypropyl palmitate. Their structures were elucidated mainly by extensive spectroscopic analysis and comparison with published data. The absolute configuration of the new metabolite was determined by electronic circular dichroism (ECD) analysis and comparison of optical rotation. Some of the isolated compounds were tested for their antimicrobial activity but no inhibition was observed. Graphical abstract: Image 1 Highlights: The phytochemical investigation of Crinum biflorum Rottb was achieved for the first time. Sixteen compounds including a new flavan-3-ol derivative were isolated and characterized. Structure elucidation was made by NMR, HRESIMS, ECD and optical rotation. The EtOAc extract showed a moderate activity against Enterococcus faecalis. The chemotaxonomic significance of their isolation is discussed.